Synthesis and Evaluation of 5-(Heteroarylmethylene)hydantoins as Glycogen Synthase Kinase-3β Inhibitors - Nicholas O. Schneider; Kendra Gilreath; Daniel J. Burkett; Martin St. Maurice; William A. Donaldson (MDPI AG, 2024)
Glycogen synthase kinase-3 (GSK-3) is a serine/threonine kinase which plays a center role in the phosphorylation of a wide variety of proteins, generally leading to their inactivation. As such, GSK-3 is viewed as a therapeutic target. An ever-increasing number of small organic molecule inhibitors of GSK-3 have been reported. Phenylmethylene hydantoins are known to exhibit a wide range of inhibitory activities including for GSK-3β. A family of fourteen 2-heterocycle substituted methylene hydantoins (14, 17-29) were prepared and evaluated for the inhibition of GSK-3β at 25 μM. The IC50 values of five of these compounds was determined; the two best inhibitors are 5-[(4'-chloro-2-pyridinyl)methylene]hydantoin (IC50 = 2.14 ± 0.18 μM) and 5-[(6'-bromo-2-pyridinyl)methylene]hydantoin (IC50 = 3.39 ± 0.16 μM). The computational docking of the compounds with GSK-3β (pdb 1q41) revealed poses with hydrogen bonding to the backbone at Val135. The 5-[(heteroaryl)methylene]hydantoins did not strongly inhibit other metalloenzymes, demonstrating poor inhibitory activity against matrix metalloproteinase-12 at 25 μM and against human carbonic anhydrase at 200 μM, and were not inhibitors for Staphylococcus aureus pyruvate carboxylase at concentrations >1000 μM.